Designing Wildlife Corridor Along Cikapundung River in Bandung Urban Area (Indonesia) based on Comparation with Kamo River in Kyoto (Japan) - Evita Izza Dwiyanti; Shozo Shibata; Ryo Nukina; Tien Lastini; Endang Hernawan (HAYATI Journal of Biosciences, 2021)
Cikapundung is a river connecting wildlife habitat in two open green space areas; there are Tahura Djuanda and Bandung Zoo. Now, these habitats are fragmented due to intervention by urban activities in the Cikapundung River boundary. One of the proposed solutions is to develop a wildlife corridor along the Cikapundung River. The purpose of this study is to identify the landcover of the Cikapundung River, analyze the potential area which can be developed into a wildlife corridor, designing the landscape of the corridor tailored to the needs of the wildlife, and comparing the condition of the Cikapundung River boundary with Kamo River in Kyoto, Japan. Primary data is landcover of Cikapundung River boundary obtained through on-screen digitizing from satellite imagery using ArcMap. Secondary data are the biodiversity list in Cikapundung River riparian area and its ecological description. Cikapundung River border has several land cover types; the highest percentage of the landcover is tree canopy 62.2%, followed by buildings 31.0%. As a result of the comparison Cikapundung River has a more significant vegetation species; however, Kamo River has a more significant number of wildlife species. In the design planning, 14 vegetation species have been selected according to 26 target wildlife species' needs.